Biafra Agitation: Analysis and Implications for Nigeria - Bassey, Imaobong (ABUAD Journal of Social and Management Sciences, 2023)
The resurgence of Biafra agitation in South-Eastern Nigeria has its negative effects on regional and national security. As a result of these protests and the resulting conflicts between Biafra activists and the security forces, economic activities have also been hampered in the affected areas. This research analyses the implications of the various Biafra agitations on Nigeria’s security. The research adopts the qualitative research methodology. It relies on data generated through interviews and other secondary sources, and content analysis. The research recommends that Igbo people should be aware of their tenacious sense of community and put it into action in all areas of their existence rather than the agitation for a separate and independent country. Strengthening weak institutions, political inclusion, and economic restructuring are identified here as some of the measures that could contribute to addressing the conflict.